Effect Of Pressurized Drilling Methods On The Lateral Load Capacity Of Drilled Shafts - A Practical Insight And An Analytical Approach - Özgür Bezgin (Deep Foundations Institute, 2009)
This paper presents observations on the installation of drilled shafts from two construction projects and an academic study with experimental and analytical parts. The construction projects involved the use of pressurized drilling methods. The experimental part of the academic study involved the use of the auger drilling method. The analytical part of the academic study investigated the effect of drilling methods on the soil-structure interaction and the behavior of drilled shafts under lateral loads. The concept of ?free-length? is introduced for the lateral load design of pressure-drilled shafts that are thought to be fully embedded within a soil media. The academic part of the study presented herein was conducted in Rutgers, the State University of New Jersey.